Selected Chapters of Electric Drives (СО) e-course - Suvorkova, Е. Е. specialist in the field of electrical engineering Assistant of Tomsk Polytechnic University 1985- (TPU Moodle, 2016)
The course "Selected chapters of electric drive "covers the basic theory and practice of electric drive. AC and DC electric drives properties, characteristics, coordinate control methods and controlling principles are considered. The course is presented by seven sections, for consolidation the theoretical material practical training is provided. To control the retention of the material for each module the self- control issues, as well as special tests are available. Knowledge acquired in the study of course will help students: to become highly qualified specialists, capable for electric drive design and research it competently; be able to formulate objectives in the field of electric drive; analyze and solve them using the resources available in English.